Slab Planning Of A 5-Storey Apartment Building On Jalan Pemuda Semarang - Mahbub Ubaidillah; Djupri Nurahman; Sumarman Sumarman (Riviera Publishing, 2025)
Poured concrete is made based on the standards applied. A table with a practical plate design is a design table that is easy to use in Iapangan and can be used as a reference material for engineers. The plate in question is a conventional double-sided double-reinforced concrete plate according to SNI 1726:2019, the design is used by Iangsung for the calculation of the Ientur moment, and the results are compared with the results of structural analysis using the ETABS 18 application. The results of the calculation using the direct design method and the existing application show almost the same trend, although the values are not much different. Ms. Excel is used as a tool to calculate plate designs with various styles. The variable parameters are the size of the span, the size of the baIok and koIom, the life load, f' c and f'y. The values obtained are presented in the form of niIai moment Ientur and distance of the Age and presented in the form of a calculation table.